Psychological impact of injuries sustained in motor vehicle crashes: systematic review and meta-analysis. Issue 9 (8th September 2016) - Craig, Ashley; Tran, Yvonne; Guest, Rebecca; Gopinath, Bamini; Jagnoor, Jagnoor; Bryant, Richard A; Collie, Alex; Tate, Robyn; Kenardy, Justin; Middleton, James W; Cameron, Ian
Abstract : Objective: The aim of this meta-analysis was to determine the psychological impact associated with motor vehicle crash (MVC)-related physical injuries. Design: Systematic review and meta-analysis. Data sources: Multiple search engines included MEDLINE (via OVID), PsycINFO and Embase, and studies were sourced from scientific journals, conference papers and doctoral theses. Study selection: A high-yield search strategy was employed. Terms like 'psychological distress', 'depression', 'PTSD' and 'motor vehicle accident' were employed. These key words were run primarily and secondary searches were then conducted in association with the major injury types. Studies needed to compare psychological distress in people injured in an MVC with uninjured controls who had not recently experienced an MVC. Data extraction: Searches resulted in the identification of 2537 articles, and after eliminating duplicates and studies not meeting inclusion criteria, 24 studies were selected involving 4502 injured participants. These studies were entered into separate meta-analyses for mild to moderate traumatic brain injury (mTBI), whiplash-associated disorder (WAD) and spinal cord injury (SCI). Results: Elevated psychological distress was associated with MVC-related injuries with a large summary effect size in WAD (0.90), medium to large effect size in SCI (0.69) and small to medium effect size in mTBI (0.23). No studies meeting inclusion criteria were found for burns, fractures and low back injury. Increased psychological distress remains elevated in SCI, mTBI and WAD for at least 3 years post-MVC. Conclusions: Rehabilitation strategies are needed to minimise distress subsequent to MVC-related physical injuries and the scientific robustness of studies requires improvement.